An Improved Key Management Scheme for Hierarchical Wireless Sensors Networks - Abdoulaye Diop; Yue Qi; Qin Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Key management play a central role for protecting communication in WSNs. Due to the limited memory resources and energy constraints, complex security algorithms cannot be used in sensor networks. Therefore, to secure data communication and well balance between the security level and the associated energy consumption is a challenging task. In this paper, we present an Improved Key management Scheme for Securing communication in Hierarchical Wireless Sensors Networks (IKS). The proposed technique based on symmetric key mechanism, generates and distributes the keys within a cluster efficiently and updates periodically keys to mitigate the node compromise attack. We provide a detailed security analysis of our IKS protocol and show its advantages in avoiding node capture attack and several serious attacks from malicious nodes. Finally, using NS-2 simulator, the results shows that IKS provides energy saving and has low communication overhead and end to end delay compared to existing key management schemes. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4241